2008
DOI: 10.1093/treephys/28.11.1661
|View full text |Cite
|
Sign up to set email alerts
|

Fruit development, not GPP, drives seasonal variation in NPP in a tropical palm plantation

Abstract: We monitored seasonal variations in net primary production (NPP), estimated by allometric equations from organ dimensions, gross primary production (GPP), estimated by the eddy covariance method, autotrophic respiration (R(a)), estimated by a model, and fruit production in a coconut (Cocos nucifera L.) plantation located in the sub-tropical South Pacific archipelago of Vanuatu. Net primary production of the vegetative compartments of the trees accumulated steadily throughout the year. Fruits accounted for 46% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…Our findings are consistent with other studies on apple trees of different growing conditions and varieties (Palmer, 1988;Minchin et al, 1997;Faqi et al, 2008), while a similar incidence of fruit production on total NPP was also found in other agro-ecosystems, such as a coconut palm plantation (Navarro et al, 2008), peach (Chalmers and van den Ende, 1975), orange (Liguori et al, 2009) and kiwifruit orchards (Rossi et al, 2007). For comparison with other croplands see Ciais et al (2010).…”
Section: Annual and Seasonal C Allocation Patternsupporting
confidence: 93%
“…Our findings are consistent with other studies on apple trees of different growing conditions and varieties (Palmer, 1988;Minchin et al, 1997;Faqi et al, 2008), while a similar incidence of fruit production on total NPP was also found in other agro-ecosystems, such as a coconut palm plantation (Navarro et al, 2008), peach (Chalmers and van den Ende, 1975), orange (Liguori et al, 2009) and kiwifruit orchards (Rossi et al, 2007). For comparison with other croplands see Ciais et al (2010).…”
Section: Annual and Seasonal C Allocation Patternsupporting
confidence: 93%
“…A significant relationship between the number of days of exposure to high temperature and the percentage of fruit set has been reported in many greenhouse and field-grown crops (Vara Prasad et al, 2000; Wubs et al, 2009b). Abortion of female flowers or young fruits is common in coconut even when they are grown under favourable climatic conditions (Navarro et al, 2008). Within plant competition between organs is based on the source-sink relationships, representing the supply and demand of assimilates.…”
Section: September 2015mentioning
confidence: 99%
“…Within plant competition between organs is based on the source-sink relationships, representing the supply and demand of assimilates. The cause of seasonal variation in net primary productivity of coconut was due to the differences in fruit development and not due to the gross assimilate production under tropical climatic conditions (Navarro et al, 2008). Therefore, it could be assumed that the variation in sink strength of a palm is more critical than the variation in source strength in determining the variation in fruit set.…”
Section: September 2015mentioning
confidence: 99%
See 2 more Smart Citations